Is a bridge even possible over troubled waters? The field of special education negates the overrepresentation of minority students: a DisCrit analysis. Issue 6 (2nd November 2019) - Connor, David; Cavendish, Wendy; Gonzalez, Taucia; Jean-Pierre, Patrick
ABSTRACT: In this article we challenge recent research within the field of special education reports an underrepresentation of all minorities in disability categories. First, we contrast these findings with selections from a large body of diverse and innovative work by scholars of overrepresentation, while recognizing the dearth of use of findings in these studies. Second, we illustrate a field of special education that has been epistemologically divided from its inception, and discuss repercussions of this schism for researching overrepresentation. Third, we call attention to color evasion within the field of special education, and to counter this, invoke Disability Critical Race Studies (DisCrit) to critique and rethink how overrepresentation can be conceptualized and researched. Fourth, we discuss some challenging issues raised by our critique. Suggestions for future research on overrepresentation are shared.